SWItching On Epidermal Cell Fate - Perdigoto, Carolina N. (Cell Stem Cell, 2013)
Chromatin regulatory complexes are well known regulators of stem cell fate; however, the mechanisms regulating their activity are not well understood. In this issue of Cell Stem Cell, Bao et al. (2013) show that ACTL6a inhibits targeting of the SWI/SNF complex to differentiation genes, thereby preserving the epidermal progenitor state.